Serum cholinesterase as a new nutritional indicator for predicting weaning failure in patients - Liu, Jiaping; Shao, Tianyu; Chen, Hanwen; Ma, Chenyang; Lu, Xiaohui; Yang, Xiaoming; Song, Kang; Wang, Lu; Lei, Shu; Wang, Dafen (Frontiers in Medicine, 2023)
Aim: To investigate the effect of patient serum Cholinesterase (SCHE) concentration on weaning failure with invasive mechanical ventilation (IMV) and predictors of ventilator weaning failure. To further assess the nutritional status of patients before the autonomic breathing test (SBT) through nutrition scores, to explore the association between SCHE and nutritional status and better weaning strategies. Method: A retrospective observational study was conducted at a university hospital. The sample was collected from 227 patients with IMV over 48 hours who underwent SBT before weaning.Relevant experimental samples and data collection were analyzed at the time of patient admission and before the start of the day of SBT. Results: Weaning was successful in 127 patients and failed in 100 patients. Depending on the difficulty of weaning, 55 of these patients had difficulty weaning and 45 had long-term weaning. Experimental data collected on the day of SBT showed that SCHE concentrations were higher in patients with successful weaning than in those with failed weaning (4514 vs 3190 P<0.01). The critical value for predicting weaning failure was SCHE 3228u/l (P<0.01). Ventilator weaning failure was predicted by multifactorial logistic regression analysis of SCHE, heart rate, and PAO2 before SBT, with SCHE predicting ventilator weaning failure (AUC 0.714; 95% CI 0.647-0.782) better than heart rate (AUC 0.618; 95% CI 0.545-0.690), PAO2 (AUC 0.59; 95% CI 0.515-0.664). And the SCHE concentration was strongly correlated with the patient's weaning difficulties (P<0.01). The Nutrition Risk in Critically ill(NUTRIC)score was also significantly correlated with SCHE according to Spearman's correlation analysis (P<0.01). Conclusions: We found that patients with weaning failure had lower SCHE values than those with successful weaning. Before SBT SCHE, heart rate and PAO2 were independent predictors of weaning failure, patients with SCHE below 3228u/l should be carefully evaluated before weaning. Weaning failure in patients may be related to malnutrition.